The Economic Growth Impact of Hurricanes: Evidence from U.S. Coastal Counties - Strobl, Eric (The Review of Economics and Statistics, 2011)
I estimate the impact of hurricane strikes on local economic growth rates. To this end, I assemble a panel data set of U.S. coastal counties' growth rates and construct a novel hurricane destruction index that is based on a monetary loss equation, local wind speed estimates derived from a physical wind field model, and local exposure characteristics. The econometric results suggest that a county's annual economic growth rate falls on average by 0.45 percentage points, 28%% of it due to richer individuals moving away from affected counties. I also find that the impact of hurricanes is netted out in annual terms at the state level and does not affect national economic growth rates at all. © 2011 The President and Fellows of Harvard College and the Massachusetts Institute of Technology.